Diagnostic Testing for Kansas Wheat Viruses - Trout, Landon; Day, Chandler; Redila, Carla; Fellers, John; O'Mara, Judy (My University, 2023)
The wheat streak mosaic virus complex consists of three viruses that are visually indistinguishable and often present together. These viruses are Wheat streak mosaic virus (WSMV), Triticum mosaic virus (TriMV), and High Plains wheat mosaic virus (HPWMoV). Together, these viruses cause millions of bushels of yield loss to farmers every year and are of great interest to plant breeders. To determine which pathogens are present in infected plant tissue, samples were taken and analyzed by enzyme-linked immunosorbent assay (ELISA) and reverse transcription polymerase chain reaction (RT-PCR). This research will investigate regional virus makeup and compare results of RT-PCR and ELISA based diagnostics. Sixty-three samples were collected from various cultivars and multiple locations in Kansas and tested with ELISA. Eighteen samples tested positive for WSMV, two samples tested positive for TriMV, and one sample tested positive for HPWMoV. To compare the results to a more sensitive diagnostic assay, RT-PCR was performed and compared to ELISA results. Of the positive ELISA samples, four samples were false positives, and two samples were false negatives. This shows that ELISA has an 80.6% accuracy rate at correctly identifying wheat viruses compared to RT-PCR. Additionally, increases in TriMV infection were detected in Joe, Hamilton, and Dallas; wheat varieties with resistance to WSMV.
Keywords: Wheat; Virus; RT-PCR; ELISA; Plant diagnostics; USDA NIFA 2019-67032-29071